Pemikiran Hukum Tuan Guru Nahdatul Wathan Tentang Kepemimpinan Perempuan dalam Islam - Irwan Sasmita Muhammad (JURNAL PENELITIAN KEISLAMAN, 2022)
This study explains the thoughts of Tuan Guru Nahdatul Wathan regarding women's leadership in Islam, where the female figure herself is always an interesting object to discuss. Whether or not women are allowed to become leaders is still a pro and cons among society in general, including scholars, politicians, especially from an Islamic point of view. Juridically, women's leadership is often cornered by gender perceptions that are unfavorable to women. Theologically, women's leadership is more of a dilemma because there are verses and hadiths that are understood as a form of rejection of women's leadership in Islam. Then can women become leaders in Islam and what are the patterns of thought and the relevance of Tuan Nahdatul Wathan's thoughts about women's leadership in Islam in the context of Indonesian Islam.